WISATA MINAT KHUSUS “ECOSPORT” SEBAGAI WISATA ALTERNATIF DI DESA GOBLEG, BULELENG BALI - I Nengah Alit Nuriawan (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2022)
This article aims to analyze the potential for special interest tourism in the waterfall area of ​​Gobleg Village, Buleleng, Bali to be developed as an alternative "ecosport" tourism. This study is a qualitative study whose data was collected by direct observation at the research site, then conducted interviews with the manager of the waterfall area and reviewed literature. The data that has been collected will be analyzed using a SWOT (strengths, weakness, opportunities and threats) analysis to find out that this ecosport special interest tourism potential is feasible to be developed in the waterfall tourism area in Gobleg Village. The results of the analysis show that the waterfall area in Gobleg Village has potential that can be developed more deeply, so that it can provide more benefits for managers and the economy of the community in the Gobleg Village waterfall tourist area. In addition, ecosport tourism is an alternative choice of tourist attractions and activities that can be offered to tourists, so that it will increase the selling value and interest of tourists in visiting and exploring this waterfall tourist area. This article is also expected to be able to provide a new contribution to the development of destinations that have potential that can be explored and developed further with a combination of activities packaged in one tourist activity.